Directed Self‐Assembly in "Breath Figure" Templating of Melamine‐Based Amphiphilic Copolymers: Effect of Hydrophilic End‐Chain on Honeycomb Film Formation and Wetting. Issue 2 (4th December 2017) - Yin, Hongyao; Feng, Yujun; Billon, Laurent
Abstract: Amphiphilic copolymers are widely used in the fabrication of hierarchically honeycomb‐structured films through a "breath figure" (BF) process because the hydrophilic block plays a key role in stabilising water templating. However, the hydrophilic monomers reported are mainly confined to acrylic acid and its derivatives, which largely limits understanding of the formation of BF arrays and the introduction of additional functions on porous films. The relationship between polymer composition, film microstructure and surface properties are also less documented. Herein, a novel melamine‐based hydrophilic moiety, N ‐[3‐(3‐[(4, 6‐bis[3‐(dimethylamino)propyl]amino‐1, 3, 5‐triazin‐2yl)amino]propyl(methyl)amino)propyl]methacrylamide (ANME), was incorporated into polystyrene (PS) chains by combining atom‐transfer radical polymerisation and post‐modification to afford three well‐defined end‐functionalised PS‐PANME derivatives. These polymers were used to fabricate honeycomb films through the BF technique. Both inner and outer microstructures of the films were characterised by optical microscopy, AFM and SEM. Polymer hydrophilicity is enhanced upon increasing the PANME content, which results in variation of the film microstructure and porosity, and provokes a transition from Cassie–Baxter to Wenzel behaviour. Furthermore, the surface wettability of as‐prepared honeycomb films and corresponding pillared films is mainly governed by film morphology, rather than by the properties of the polymers. Knowledge of the relationships between polymer composition and film structure, as well as surface wettability, is beneficial to design and prepare hierarchically porous films with desirable structures and properties. Abstract : Catching droplets : A series of melamine‐based diblock copolymers were synthesised and used to fabricate honeycomb films through the "breath figure" templating technique. A molecule with too little hydrophilicity is unable to generate a porous structure, but hydrophilicity that is too strong leads to large‐sized multi‐layered pores with poor regularity (see figure).